Response to the SAMHSA Clinical Advisory: Considerations for Genetic Testing in the Assessment of Substance Use Disorder Risk - Green RP; Blum K; Lewandrowski KU; Gold MS; Lewandrowski AP; Thanos PK; Dennen CA; Baron D; Elman I; Sharafshah A; Modestino EJ; Badgaiyan RD (Substance Abuse and Rehabilitation)
Richard Paul Green,1 Kenneth Blum,2– 5 Kai Uwe Lewandrowski,5,6 Mark S Gold,7 Alexander PL Lewandrowski,8 Panayotis K Thanos,2,9 Catherine A Dennen,10 David Baron,3,11 Igor Elman,2,12 Alireza Sharafshah,13 Edward J Modestino,14 Rajendra D Badgaiyan15 1Precision Translational Medicine, LLC, San Antonio, Tx, USA; 2Department of Molecular Biology and Adelson School of Medicine, Ariel University, Ariel, Israel; 3Center for Sports, Exercise, Global Mental Health, Western University Health Sciences, Pomona, CA, USA; 4Institute of Psychology, ELTE Eötvös Loránd University, Budapest, Hungary; 5Center for Advanced Spine Care of Southern Arizona and Surgical Institute of Tucson, Tucson, AZ, USA; 6Department of Orthopaedics, Fundación Universitaria Sanitas, Bogotá, DC, Colombia; 7Department of Psychiatry, Washington University, School of Medicine, St. Louis, Missouri, USA; 8Department of Biological Sciences, Dornsife College of Letters, Arts & Sciences, University of Southern California, Los Angeles, CA, USA; 9Behavioral Neuropharmacology and Neuroimaging Laboratory, Department of Pharmacology and Toxicology, Jacobs School of Medicine and Biomedical Sciences, Clinical Research Institute on Addictions, University at Buffalo, Buffalo, NY, USA; 10Department of Family Medicine, Jefferson Health Northeast, Philadelphia, PA, USA; 11Department of Psychiatry, Stanford University School of Medicine, Palo Alto, CA, USA; 12Department of Psychiatry, Harvard University School of Medicine, Cambridge, MA, USA; 13Cellular and Molecular Research Center, School of Medicine, Guilan University of Medical Sciences, Rasht, Iran; 14Brain & Behavior Laboratory, Department of Psychology, Curry College, Milton, Massachusetts, USA; 15Department of Psychiatry, Texas Tech University Health Sciences, School of Medicine, Midland, TX, USACorrespondence: Rajendra D Badgaiyan; Kenneth Blum, Email badgaiyan@gmail.com; drd2gene@gmail.com